Urban modelling for seismic prone areas - Martins, V. N. (2012)
Martins, V. N., Cabral, P., & Sousa E Silva, D. (2012). Urban modelling for seismic prone areas: The case study of Vila Franca do Campo (Azores Archipelago, Portugal). Natural Hazards and Earth System Science, 12(9), 2731-2741. https://doi.org/10.5194/nhess-12-2731-2012